Direct SPD-processing to achieve high-ZT skutterudites. (15th October 2018) - Rogl, G.; Grytsiv, A.; Anbalagan, R.; Bursik, J.; Kerber, M.; Schafler, E.; Zehetbauer, M.; Bauer, E.; Rogl, P.
Abstract: For mass fabrication of thermoelectric generators a fast, cheap and simple method is required to produce high ZT leg material. It is well known that severe plastic deformation (SPD) enhances the density of defects and dislocations, and also refines the grains to nano-size. These are the essential key parameters for low thermal phonon conductivity. Consequently and as a first example, SPD via high-pressure torsion (HPT) at elevated temperatures in protective gas atmosphere was used to directly consolidate and plastically deform commercial p-type skutterudite powder, DDy Fe3 CoSb12, (DD stands for didymium) into a dense thermoelectric solid. The HPT-sample exhibited a high figure of merit, ZT > 1.3 at 773 K, much higher than that of the hot-pressed reference sample (HP) from the same powder. The ZT achieved is comparable with ZTs of corresponding high energy ball milled and hot pressed samples (HBM-HP) as well as of ball milled, hot pressed plus HPT processed skutterudites (BM-HP-HPT). The thermoelectric efficiency is even 4% higher. Synchrotron measurements were performed at temperatures from 300 to 825 K in order to evaluate the changes in grain size and dislocation density of the CP-HPT samples before, during and after annealing. SEM and TEM images served to give a better insight into the temperature dependent diversification of the new material. Due to grain refinement and enhanced dislocation density, the CP-HPT material exhibits higher hardness values than the reference sample. The elastic moduli are, within the error bar, the same. With large high-pressure torsion facilities at hand, a new, fast and therefore cheap mass production of thermoelectric leg material directly from powders can be envisaged. This new production technique furthermore warrants high figures of merit but excludes time-consuming ball milling and hot-pressing steps. Graphical abstract: Image 1